PELATIHAN, KOMITMEN DAN PENGALAMAN KERJA TERHADAP KINERJA KARYAWAN PT. KEMBANG MAS GLOBAL INDOTRADE SURAKARTA - Qoirudin Qoirudin (JURNAL ILMIAH EDUNOMIKA, 2021)
The company seeks to improve the quality of human resources. Improving employee performance requires planned activities from the company, improvement and development of a quality culture in order to compete with other companies. This study aims to determine and explain training, commitment and work experience to the performance of employees of PT. Kembang Mas Global Indotrade Surakarta. The study sample was 75 employees and used multiple linear regression methods. The results of this study are the variables of training, commitment and work experience together or simultaneously have a positive and significant effect on the performance of employees of PT. Kembang Mas Global Indotrade Surakarta. Partially, training has a positive and significant effect on employee performance. Commitment has a positive and significant effect on employee performance. Work experience has a positive and significant effect on employee performance. Employee performance variables can be explained by the variables of training, commitment and work experience of 41.2% and 58.8% influenced by other variables. Keywords: training, commitment, work experience, employee performance